The Chironomid Microbiome Plays a Role in Protecting Its Host From Toxicants - Sela, Rotem; Halpern, Malka (Frontiers in Ecology and Evolution, 2022)
Organisms are assemblages of the host and their endogenous bacteria, which are defined as microbiomes. The host and its microbiome undergo a mutual evolutionary process to adapt to changes in the environment. Chironomids (Diptera; Chironomidae), are aquatic insects that grow and survive in polluted environments; however, the mechanisms that protect them under these conditions are not fully understood. Here we present evidence that the chironomids' microbiome enables them to survival in polluted environments. It has been demonstrated that about 40% of the microbiota that inhabit Chironomus transvaalensis egg masses and larvae has the potential to detoxify different toxicants. Metagenomic analysis of Chironomus ramosus larvae demonstrated the presence of genes in the insects’ microbiome that can help the insects to survive in hostile environments. A set of experiments demonstrated that short exposure of C. transvaalensis larvae to metals significantly changed their microbiota composition in comparison to unexposed larvae. Another experiment, that followed Koch's postulates, demonstrated that disinfected C. transvaalensis larvae can survive toxic lead and chromium exposure when they are recolonized with bacteria that can detoxify these toxic metals. This accumulating research, points to the conclusion that the chironomid microbiome plays a role in protecting its host from toxicants.